PETA PEMIKIRAN M. QURAISH SHIHAB DALAM WACANA STUDI AL-QUR’AN DI INDONESIA - Farid Hasan (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2021)
The Indonesian public has known this famous Indonesian mufassir quite well. Not only in lectures and seminars, but also widely known by the general public. So that at a glance it will be easier to explain who the figure of M. Quraish Shihab is in front of general readers. Nevertheless, apparently there are still things that are academic in nature, which are not widely known by the public. In the context of methodology, for example, Tafsir al-Misbah has special characteristics that color its interpretation and describe the intellectual expression of the interpreter in understanding the meaning of the verses of the Qur'an. Tafsir al-Misbah successfully combines the presentation of the surahs of the Qur'an with al-adabi al-ijtima'i style with correlative tahlili method. That is, Tafsir al-Misbah although patterned adabi al-ijtima'i (social-cultural style) does not leave the unity of the message in each surah of the Qur'an. The style of thought and its distinctive tendencies have colored enough in the discourse of the study of the Qur'an in Indonesia. Through his magnum oppus, Quraish Shihab has become one of the important references in studying the dynamics of al-Qur'an studies in Indonesia. The characteristics of Tafsir al-Misbah that emphasize the balance aspect of the approach, namely combining the linguistic approach with the contextual paradigm, succeeded in presenting the meanings of the Qur'an that are functional, down-to-earth, straightforward and easily understood by all elements of Indonesian society.